Investigating the Relationship between Organizational Culture and Organizational Justice among Health Workers in Turkey - KAYA, Servet (Journal of Economics and Behavioral Studies, 2015)
To achieve profits, management has to put in place several inputs. Of all the inputs, human resources or the employees are the most important and yet, the most unpredictable. Research has identified organizational culture and organizational justice as two factors enabling employee satisfaction. Upon, their identification, research has continued into these areas as two separate fields and has come up with several results. However, little is known on how these two interrelate and their effect on one another. This study sought to provide this information by investigating the correlation between these two factors. To do this, a cross-sectional survey was carried out among 223 health workers from a public hospital in Malatya, Turkey during May and June 2014. Out of a maximum of 20, organizational culture and organizational justice received mean scores of 11.4 ± 2.3 and 14.0 ± 4.8 respectively. Correlation analysis showed that almost all the domains of organizational culture had a statistically significant moderately positive relationship (0.434 ≤ r ≤ 0.636) with the domains of organizational justice with the exception of the power domain. This study finds a statistically positive correlation between overall justice scores and overall culture scores. However the correlation between them is moderate indicating that it is possible that other factors are equally or even more important in their determination. Thus, while managers can use organizational culture as an indication of organizational justice, they should not totally rely on one as a measure of the other.